Assessing the effects of tourism on the spread of HIV and AIDS in Malaysia using susceptible infected removed models / Ofosuhene Okofrobour Apenteng - Ofosuhene Okofrobour , Apenteng (2017)
The spread of human immunodeficiency virus (HIV) infection and the resulting acquired immune deficiency syndrome (AIDS) is a major health concern in many parts of the world. Tourists may be exposed to health risks before, during and after leaving their countries of origin. Unfortunately, knowledge about the health status of tourists is often limited because they are often excluded from surveys. Tourism has been classified as playing a pivotal role in the spread of HIV and AIDS epidemic. However, it has not been well recognized that tourism is one of the leading activities contributing towards the spread of HIV and AIDS. In this thesis, we developed a mathematical models for HIV and AIDS epidemic to assess how the effect of outbound and inbound tourism have affected the spread of HIV and AIDS incidences in Malaysia. Applying the next generation matrix method to obtain the various basic reproduction numbers, the models were calibrated to HIV and AIDS incidence data in Malaysia using a Markov chain Monte Carlo (MCMC) approach to understand the impact of model-based estimation in light of uncertain parameters on the spread of HIV and AIDS. The models dynamics are analysed under these four scenarios: with the effect of outbound (Model I), inbound tourism (Model II), condom as preventive measure (Model III) and new born babies with HIV through sexual activities which runs through all the three models. The models show distinctive characteristics of positive equilibrium which depicts that both locally and globally are asymptotically stable under particular conditions. These confirmed the basic reproduction numbers that were calculated based on the estimated parameters. The basic reproduction numbers for Model I, Model II and Model III are 1.0262e-06, 7.8060e-01 and 7.1960e-01, respectively. Although, our results show that disease models are stable, this indicates that HIV and AIDS continue to persist at equilibrium level. This is a good indicator from the public health point of view since the aim is to stabilize the epidemic at the disease-free equilibrium and this will assist public health policy decision makers to forecast and predict HIV/AIDS incidences. We further incorporate the use of condoms as a preventive measure to ascertain its impact on the spread of HIV and AIDS incidence. Thus, if condom as preventive measures are introduced, it reduces the HIV and AIDS incidences. The results indicate that with the persistent inflow of inbound tourists into the country, the disease status has increased. The results also suggest that the government must put more control on illegal prostitution, unprotected sexual activity as well as to emphasize the prevention policies that include safe sexual activity through tourism board campaigns. They should encourage free health care medical examinations for outbound Malaysian tourists after they have returned home. This will assist to reduce the rate of outbound tourists unknowingly spreading HIV.